2014
DOI: 10.18632/oncotarget.2990
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid precursor-like protein 2 (APLP2) affects the actin cytoskeleton and increases pancreatic cancer growth and metastasis

Abstract: Amyloid precursor-like protein 2 (APLP2) is aberrantly expressed in pancreatic cancer. Here we showed that APLP2 is increased in pancreatic cancer metastases, particularly in metastatic lesions found in the diaphragm and intestine. Examination of matched human primary tumor-liver metastasis pairs showed that 38.1% of the patients had positive APLP2 expression in both the primary tumor and the corresponding liver metastasis. Stable knock-down of APLP2 expression (with inducible shRNA) in pancreatic cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 22 publications
6
36
0
Order By: Relevance
“…At present, the signalling pathways by which APLP2 wields its effects in cancer cells are poorly understood. Pandey et al (5) determined that loss of APLP2 decreased cortical actin and increased intracellular actin filaments in pancreatic cancer cells, reducing the ability of these cells to migrate and invade. Other studies demonstrated that APLP2 can regulate major histocompatibility complex class I molecule expression in cancer cells and increase cancer immune evasion (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the signalling pathways by which APLP2 wields its effects in cancer cells are poorly understood. Pandey et al (5) determined that loss of APLP2 decreased cortical actin and increased intracellular actin filaments in pancreatic cancer cells, reducing the ability of these cells to migrate and invade. Other studies demonstrated that APLP2 can regulate major histocompatibility complex class I molecule expression in cancer cells and increase cancer immune evasion (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The human APLP2 gene is located at 11q24 and is expressed in the majority of tissues (4). It has been demonstrated that APLP2 expression is involved in the development of a number of cancer types, including pancreatic, colon, breast and prostate cancer (5). APLP2 has been associated with certain characteristics of cancer cells, including abnormal growth, migration and invasion, which indicates that APLP2 may significantly affect the development and progression of cancer (6); however, the expression and function of APLP2 in RCC remains undefined.…”
Section: Introductionmentioning
confidence: 99%
“…As reported previously, APLP2 has biochemical functions related to cell migration, signaling, adhesion, proliferation, and healing [9,13,17,32]. Recently, dysregulation of APLP2 has been found in multiple cancer types, such as colorectal cancer, lung cancer, breast cancer, pancreatic cancer, and Ewing's sarcoma, and to be involved in abnormal growth, invasion, and metastasis [1,2,16,21,24,29]. However, the expression pattern (increase or decrease) of APLP2 is found inconsistent from cancer to cancer, though the consequences are not really clear [22].…”
Section: Introductionmentioning
confidence: 89%
“…Full automation was provided by custom software that allows parallel event coordination and therefore near 100% MS duty cycle through use of two trapping and analytical columns. RP columns were slurry packed in-house with 3 m Jupiter C 18 (Phenomenex, Torrence, CA) into fused silica columns that were 40 Data acquisition lagged the gradient start and end times by 15 min to account for column dead volume allowing for the highest throughput when running in two-column operation mode, so that the columns could to be washed (shortened gradients) and re-generated off-line without any cost to the duty cycle.…”
Section: Experimental Design and Statistical Rational: Lc-ms And Lc-imentioning
confidence: 99%
“…Of significant interest was the detection of MEPCE, FAP and APLP2, which in addition to ranking high in at least 50% of HPA breast cancer stains, have been positively correlated with invasive and metastatic potential. RNA methyltransferase (MEPCE -7SK snRNA methylphosphate capping enzyme) has been found to be overexpressed in highly tumorigenic breast cancer stem cells (36,37), prolyl endopeptidase FAP (FAP) is a cell surface glycoprotein serine protease that participates in malignant cell invasiveness by degrading the extracellular matrix (38) and amyloid-like protein 2 (APLP2) has higher expression within invasive breast cancer because it promotes rearrangement of the actin cytoskeleton by increasing cortical actin (39,40). Detection of these proteins illustrates the power of DTM analyses for finding new information in a high throughput unfractionated approach while simultaneously targeting specific proteins.…”
Section: Dtm With Lc-ims-ms Compared With Lc-ms and Lc-ms/msmentioning
confidence: 99%